Trends in Worker Demand for Union Representation - Farber, Henry S. (American Economic Review, 1989)
The dramatic decline in the demand for union representation among nonunion workers over the last decade is investigated using data on worker preferences for union representation from four surveys conducted in 1977, 1980, 1982, and 1984. Relatively little of the decline can be accounted for by shifts in labor force structure. However, virtually all of the decline is correlated with an increase in the satisfaction of nonunion workers with their jobs and a decline in nonunion workers ' beliefs that unions are able to improve wages and working conditions.